2018
DOI: 10.1016/j.envres.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to perfluoroalkyl substances and associations with serum thyroid hormones in a remote population of Alaska Natives

Abstract: Perfluoroalkyl substances (PFASs) are known to accumulate in traditional food animals of the Arctic, and arctic indigenous peoples may be exposed via consumption of subsistence-harvested animals. PFASs are suspected of disrupting thyroid hormone homeostasis in humans. The aim of this study is to assess the relationship between serum PFASs and thyroid function in a remote population of Alaska Natives. Serum samples were collected from 85 individuals from St. Lawrence Island, Alaska. The concentrations of 13 PFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Human studies suggested that prenatal PFOA/PFOS exposure was significantly associated with testosterone/estradiol in male infants, progesterone levels, glucocorticoid levels, and DHEA levels in cord blood samples of both sexes [27, 40]. In addition, effects of PFAS exposure on thyroid hormone homeostasis may differ across sexes [41]. The hormonal effects of PFAS may differently affect the neurobehavioral development of males or females.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies suggested that prenatal PFOA/PFOS exposure was significantly associated with testosterone/estradiol in male infants, progesterone levels, glucocorticoid levels, and DHEA levels in cord blood samples of both sexes [27, 40]. In addition, effects of PFAS exposure on thyroid hormone homeostasis may differ across sexes [41]. The hormonal effects of PFAS may differently affect the neurobehavioral development of males or females.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have tested the effect of PFASs on thyroid hormone homeostasis in healthy adults. The results were inconsistent and showed no effect [ 254 , 345 , 391 , 392 , 393 , 394 , 395 , 396 , 397 , 398 , 399 , 400 , 401 , 402 , 403 , 404 ], increase [ 254 , 401 , 405 , 406 ] or decrease [ 344 , 398 ] in TSH levels after exposure to PFASs. No effect [ 254 , 345 , 398 , 399 ], increase [ 254 , 392 , 395 , 396 , 397 , 402 , 404 , 406 ] or decrease [ 344 , 401 , 406 ] in T3 levels and no effect [ 254 , 393 , 395 , 396 , 397 , 399 , 404 , 406 ], increase [ 254 , 344 , 345 , 394 , 397 , ...…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
“…In a study evaluating the associations between serum PFAS concentrations and circulating thyroid hormones in a population of Alaska natives it was suggested that the effects of PFAS exposure on thyroid hormone homeostasis may differ between sexes. Indeed, PFOS and PFNA were positively associated with circulating free triiodothyronine (FT3) in females and negatively associated with FT3 in males participants ( 61 ).…”
Section: Introductionmentioning
confidence: 99%